Dynamic behavior of plates on elastic foundation under moving harmonic load - Maiti P.R.; Saha R. (My University, 2025)
The dynamic behavior of a finite plate resting on elastic foundation subjected to moving harmonic load has been investigated. The rigid pavement systems have been selected as models of the plate on elastic Winkler foundation. The single moving concentrated load with harmonic load variation with constant velocity and frequency has been investigated. The effects of foundation stiffness and load positions on the plate have been studied. Results indicate that the foundation stiffness and the velocity and frequency of the moving load have significant effects on the dynamic response of the plate and on velocities.